Kedudukan Kompilasi Hukum Islam Dalam Legalitas Pernikahan Di Indonesia - Gilang Rizki Aji Putra; Ahmad Mukri Aji (SALAM: Jurnal Sosial dan Budaya Syar-i, 2018)
Islam is a religion of rahmatan lil'alamin, which is easy to adapt to grow in all places and times, such as in marriage. For ethnic groups who have customs and culture, marriage is a very important thing for humans in life which is carried out in an honorable ceremony. On the other hand, Islam also regulates marriage procedures that must be carried out by Muslims. Marriage is something that is very important in human life, therefore a marriage must be in accordance with religious provisions and statutory regulations so that the marriage gets legal certainty and protection. However, nowadays in society there is a tendency for marriage to be carried out in a sirri way, this tendency often occurs, especially for a man's second marriage or polygamy. This study wants to reveal the position of polygamous marriage in a family law perspective and reveal whether or not polygamous marriage is legal according to the UUUP and according to Islamic law.Keywords: Com Marriage, Law and AqadAbstrak:Islam is a religion of rahmatan lil'alamin, easy to adapt to growth and development wherever and whenever, such as in marriage. For people who have customs and culture, marriage is a very important thing in human life, and is carried out in a solemn ceremony. On the other hand, Islam also regulates marriage procedures that must be carried out by Muslims. Marriage is a very important thing in human life, so marriage must be in accordance with religious regulations and statutory regulations, so that marriage can be determined and protected by law. But nowadays society has a tendency to get married, and this tendency often occurs, especially for men with second marriages or polygamy. This study wants to reveal the position of polygamous marriages in a family law perspective and reveal whether or not polygamous marriages are legal according to UUUP and according to Islamic law.Kata Kunci: Pernikahan, Hukum, dan Aqad